Kadar Protein Dan Organoleptik Yoghurt Jamur Tiram Dengan Penambahan Ekstrak Buah Mangga Dan Konsentrasi Starter Yang Berbeda - Setyawati, Ayu, Dra. Suparti, M.Si (2015)
Oyster mushroom yoghurt is a fermented drink which is made by the help of lactic acid bacteria. The activity of lactic acid bacteria in the starter can give effect to protein content of yoghurt, in order to support this research's purpose is to the protein level and organoleptic oyster mushroom yoghurt by adding mango extract and concentration of starter. This research is held in biology laboratorium, teacher training and education programme, Muhammadiyah University of Surakarta on Desember 2014 - January 2015. Methods used in this research is completely randomized design (RAL) 2 factors. The first factor was the mango extract conxixted of 0%, 15%, 30%. The second factor was consisted consentration starter consisted starter concentration of 3%, 5%, 7%, so have 9 the combination of treatment. Based on the result of research it shows that the highest protein level is 0,246 at M0K3 treatment (mango extract 0%, starter 7%). While the lowest protein level is 0,109 at M0K1 treatment (mango ekstract )%, starter 3%).based on the research of protein level from 9 treatments, the adding of mango extract doesn't give significant effect in oyster mushroom yoghurt protein level. While the adding of starter gives significant effect in oyster mushroom yoghurt's protein level and there is interaction both of them toward the protein level. The combination of treatment which get best organoleptict result are treatments M1K1, M1K2, M1K3 with have characteristics : it isn't too thick, it has bright yellow color, it has special yoghurt aroma, and it has extreme sour to sweeten sour.